Smoking pattern among female college students in Dammam, Saudi Arabia - Manal R Koura; Ahlam F Al-Dossary; Ahmed A Bahnassy (Wolters Kluwer Medknow Publications, 2011)
Background: Smoking is the most important avoidable cause of premature morbidity and mortality in the world. The estimated annual death rate of 4.9 million people in 1999 is expected to rise to 10 million by the 2020s and 2030s, 7 million of which will occur in developing countries. Aim: The aim of the present study was to estimate the prevalence of smoking and assess its pattern among non-medical female college students in Dammam, Saudi Arabia. Materials and Methods: A cross-sectional study was conducted of 1020 female students selected from the literature and science colleges by multi-stage stratified random sampling technique with proportional allocation. Data were collected using a self-administered modified WHO Global Youth Tobacco Survey questionnaire. Results: Results revealed that occurrence of smoking among female college students was 8.6%. It was significantly higher among literature college students (12.1%) than among Science College students (3.4%). The mean age at which smoking started was 16 ± 2.4 years, with a minimum of 11 years. More than half of the students who smoked were cigarette smokers, while 43.2% were shisha smokers. There was a strong relationship between parents who smoked and daughters who smoked. The main motive for smoking was curiosity (44.3%), followed by relief of tension (26.1%). Conclusions: It may be concluded that smoking is increasing among female college students in Saudi Arabia. Accordingly, it is recommended that a preventive comprehensive health education program on smoking be initiated for females in middle schools, that stricter tobacco control measures be adopted by the government, and that anti-smoking clinics be established in colleges.